2021
DOI: 10.18240/ijo.2021.01.21
|View full text |Cite
|
Sign up to set email alerts
|

Sustained-release drug delivery systems for the treatment of glaucoma

Abstract: Glaucoma, a leading cause of irreversible blindness, affects more than 64 million people worldwide and is expected to grow in number due to the aging global population and enhanced methods of detection. Although topical therapies are often effective when used as prescribed, the drawbacks of current medical management methods include poor patient adherence, local and systemic side effects, and in some cases, limited therapeutic efficacy. Novel ocular drug delivery platforms promise to deliver differentiated dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…Another delivery system developed with PRINT R is an Envisia Therapeutics implant (ENV515) currently in phase 2 clinical trials (194). Results thus far suggest that ENV515 is effective in lowering IOP for 28 days (195,196). Results from a 12-month study found 25% IOP reduction compared to topical ophthalmic solution (195).…”
Section: Fibers Films Rods Extrusionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Another delivery system developed with PRINT R is an Envisia Therapeutics implant (ENV515) currently in phase 2 clinical trials (194). Results thus far suggest that ENV515 is effective in lowering IOP for 28 days (195,196). Results from a 12-month study found 25% IOP reduction compared to topical ophthalmic solution (195).…”
Section: Fibers Films Rods Extrusionsmentioning
confidence: 97%
“…Results thus far suggest that ENV515 is effective in lowering IOP for 28 days (195,196). Results from a 12-month study found 25% IOP reduction compared to topical ophthalmic solution (195). PRINT R shows great promise for its ability to customize polymer-based ocular drug delivery systems at the nanoscale level.…”
Section: Fibers Films Rods Extrusionsmentioning
confidence: 97%
“…A placebo-controlled multicentre Phase III trial found OTX-TP treated eyes had statistically significant IOP reduction in eight of nine time points over 20-weeks of follow-up, with only transient and minor adverse effects, most commonly dacyrocanaliculitis [ 106 ]. However, the system is reportedly no longer under development [ 107 ]. Other external routes recently considered have included topical forniceal inserts [ 108 ], subconjunctival injections [ 109 ], and micelle-laden contact lenses to achieve sustained drug release [ 110 ].…”
Section: Amd Dmo Rvo and Uveitismentioning
confidence: 99%
“… 17 In addition, large doses and frequent systemic administration can cause adverse effects. 18 Recent studies have shown that nano-carriers are useful to deliver hydrophilic or lipophilic drugs to the eye, prolong the half-life of drugs in the vitreous, and improve the bioavailability of many drugs, including proteins and peptides. 19 , 20 Interestingly, applications of polymeric nano-micelles have been tested for intraocular and surface ocular disease treatment.…”
Section: Traditional Delivery Of Ocular Drugsmentioning
confidence: 99%